Economies of Density and Productivity in Service Industries: An Analysis of Personal Service Industries Based on Establishment-Level Data - Morikawa, Masayuki (The Review of Economics and Statistics, 2011)
This study aims to empirically investigate the determinants of service industry productivity, such as economies of scale and economies of density. By using establishment-level data related to personal service industries in Japan, the study estimates the production functions for both value-added and physical output measures. In almost all the service industries examined, significant economies of scale and economies of density are observed, wherein productivity increases by 7% to 15% when the municipality population density doubles. These findings are confirmed by an estimation in which the measures of physical output are considered instead of value added.